Role of Tranexamic acid in NSAIDS induced angioedema - Chalise, Rupak; Poudel, Saroj; Bist, Manoj; Regmi, Ashim; Ghimire, Anup; Khanal, Kishor (Nepalese Respiratory Journal, 2023)
Tranexamic acid (TXA) is an antifibrinolytic agent that inhibits the conversion of plasminogen to plasmin, a key step in kallikrein activation and bradykinin formation. Tranexamic acid is used in the prophylactic management of hereditary angioedema; however, evidence for TXA in Non-Steroidal Anti-inflammatory drug-induced angioedema (NSAIDS-AE) is limited. We describe a patient who presented to the ICU department with NSAIDS-AE and was successfully treated with TXA. This case suggests that TXA may be a beneficial treatment modality in the management of NSAIDS-AE and warrants further investigation.